Gallium-V antireflective nanostructures by metal-assisted chemical etching for photodetector application - Liao, Yikai (Nanyang Technological University, 2024)
With the ability to convert light signal into electrical signal, photodetectors (PDs) have been playing a crucial role in a variety of applications like imaging, environmental monitoring and military. Group III-V compound semiconductors have been drawing intensive and extensive research interest in this field, especially Gallium-V (Ga-V) compound family. Typical representatives are gallium arsenide (GaAs) and gallium nitride (GaN). Both have direct bandgap characteristics, together with suitable bandgap energy value and commercialized availability of mass production, making them suitable for PD applications. In PD, surface reflection is regarded as the major optical loss that limits the total amount of light absorbed by the PDs. Therefore, implementation of antireflective structures is favorable in reducing the optical loss from surface reflection, leading to enhancing light absorption as well as performance of PDs. Top-down etching is a facile way to fabricate nanostructures compared with bottom-up growth method. Nonetheless, conventional wet etching is mostly isotropic which could hardly lead to effective antireflective surface texturing with high aspect ratio. Dry etching can realize well anisotropic etching. However, the ion bombardment from plasma would unavoidably result in surface damage which degrades device performance. Metal-assisted chemical etching (MacEtch) has been put forward as a novel anisotropic etching method. The plasma-free and damage-free etching characteristics enable its potential in electronic device application. Therefore, this thesis is devoted to employ effective antireflective surface texturing via MacEtch to GaAs and GaN based PDs. The goal is to improve performance of PDs. Both of GaAs and GaN will be involved in the study for applications in UV-visible and UV range for their narrow and wide bandgap characteristics respectively. Firstly, MacEtch was employed onto GaAs. The fabricated nanopillar array shows broadband UV-visible antireflective characteristic. By implementing an Indium-gallium-zine oxide (IGZO) layer coating, surface reflection can be further reduced to 10% from 40% of planar GaAs in 300 to 800 nm UV-visible spectrum range. Integration of antireflective nanopillar array and IGZO ultraviolet (UV) absorbing layer for heterostructure PD results in 30 times responsivity enhancement under 300 nm UV light illumination and 20 times in visible range compared with control Schottky device. From the aspect of UV selectivity, GaN is preferred over GaAs for PD applications in specific UV range. Therefore, secondly, GaN was adopted for UV PDs for the good selectivity to UV light from its wide bandgap characteristic. MacEtch recipe was developed on GaN in etchant mixture of potassium persulfate as oxidant and hydrofluoric acid as acid under 254 nm UV illumination with patterned Platinum (Pt) layer as catalyst. Increasing either K2S2O8 or HF concentration leads to increasing etching rate. Comparative study shows that Pt layer plays crucial role in boosting etching of GaN in MacEtch process. Thirdly, based on thermal dewetting characteristic of metals, a Pt catalyst network was employed for fabricating sub-micron scale antireflective nanoridge surface texturing via MacEtch on GaN. PDs based on undoped GaN with nanoridge texturing exhibit high responsivity of 115 A/W to 365 nm UV light compared with 18 A/W of planar GaN. Optical simulation confirms that the nanoridge structure can realize light-matter coupling into GaN for boosting light absorption. The thin oxide layer formed by MacEtch on GaN can reduce dark current. In summary, MacEtch was adopted to fabricate effective antireflective nanostructures on two widely studied photodetecting materials of Ga-V compound semiconductors. PDs based on such structures exhibit improved responsivity in their respective application wavelength ranges. As a novel anisotropic etching technique, this thesis paves the way for the application of the MacEtch in photo-sensing optoelectronics.